Simulacra of emptiness. The model as habitable space - Elena Mucelli (Agathón)
This contribution is part of a study dedicated to the architectural model as a tool able to reveal the formal generative process of the project. This text develops the topic of the relationship between space and form, further analysing the relationship between the scale of the model and the meaning it takes on in a three-dimensional representation of hollow space. In particular, the examination stems from the hypothesis that the more research is oriented towards the study of the relationship between emptiness and the human figure, the more the scale of the model chosen to experiment with spatial qualities approaches real life, a 1:1 scale, and employs an interdisciplinary approach to identify possible points of contact between research conducted in architecture, sculpture and photography.